PENURUNAN KADAR ASAM LEMAK BEBAS PADA MINYAK JELANTAH DENGAN MENGGUNAKAN ABU KALSINASI DARI BEBERAPA BAHAN ADSORBEN - Rafi Firmana Hadyanto; Ritson Purba; Daniel -; Ade Shiva Rizki (Jurusan Kimia FMIPA UNMUL, 2025)
Cooking oil has a primary function as a heat transfer medium in food processing. Repeated use of cooking oil can reduce its quality, which is often referred to as used cooking oil. Many people use cooking oil repeatedly to save money without considering the impact. The purpose of this study was to determine the results of refining used cooking oil in terms of free fatty acid (FFA) levels through the adsorption method using calcined ash from several different types of adsorbents, namely chicken eggshells, Tegillarca granosa shells, zeolite, and bricks. Based on the results of the study, the results of the FFA content of the used cooking oil sample were 2.735%. The results of the FFA content of the used cooking oil sample after being adsorbed using calcined ash from chicken eggshells, blood cockle shells, zeolite, and bricks were 0.638%, 0.464%, 1.691%, and 0.921%, respectively. Of the four adsorbent materials, the type of adsorbent obtained is calcined blood cockle shell ash which is the most effective in reducing the ALB levels of used cooking oil samples, which is 83.03%. Then followed by chicken egg shells, which is 76.67%, bricks, which is 66.32%, and commercial zeolite, which is 38.17%.